Automated analysis protocol for high resolution BOLD‐fMRI mapping of the fingertip somatotopy in brodmann area 3b. Issue 2 (25th June 2015) - Pfannmöller, Jörg P.; Schweizer, Renate; Lotze, Martin
Abstract : Background: To introduce a standardized and automatized method for functional MRI (fMRI) examinations of the cortical sensory somatotopy in large samples for investigations of the fingertip somatotopy in the primary somatosensory cortex. Methods: At 3 Tesla, T2* (spin‐spin relaxation time) weighted images (gradient‐echo echo planar imaging, voxel size 1.5 × 1.5 × 2 mm 3 ) were acquired during stimulation of the finger tips for thumb, index and middle finger on both hands, in a group of 18 healthy participants. In addition, structural T1 weighted (magnetization prepared rapid gradient echo, isotropic voxel size 1 mm) and MR‐angiography (time of flight, voxel size 0.26 × 0.26 × 0.5 mm 3 ) images were recorded. Boundary based register served to combine movement correction and registration in FreeSurfer Functional analysis stream (FS‐Fast), resulting in fine scale corrections, as revealed with FSL Possum (FSL FMRIB Software Library Physics‐Oriented Simulated Scanner for Understanding MRI) simulations. Automated data analysis was achieved by inclusion of cytoarchitectonic probability maps for calculation of functional activation in Brodmann area 3b. Draining vessel artifacts were identified using the peak value approach and the MR‐angiography. Distances were computed as the shortest connection within the gray matter. Results: The fMRI somatotopic maps agreed with the expected fingertip somatotopy in 63% of the investigated subjects, an improvement of 34% compared with FS‐Fast. Artifacts have been removed completely. Adjacent fingertips showed average distances of 8 ± 4.3 mm, and between thumb and middle finger 13.4 ± 4.8 mm was found. Distances for both hands were similar as expected from the characteristics of the fingertip spatial tactile resolution. Conclusion: The introduced evaluation procedure allowed automated analysis of the fingertip representation in excellent agreement with preceding results. J. Magn. Reson. Imaging 2016;43:479–486.